2009
DOI: 10.1183/09031936.00145307
|View full text |Cite
|
Sign up to set email alerts
|

Decreased FOXP3 expression in small airways of smokers with COPD

Abstract: CD4+CD25+ FOXP3-positive T-regulatory cells have an important role in controlling immune and inflammatory reactions. The present authors hypothesise that these cells may be involved in the pathogenesis of chronic obstructive pulmonary disease (COPD). The aim of the present study was to characterise the expression of FOXP3 in large and small airways of nonsmokers, smokers with normal lung function and COPD patients.A total of 19 nonsmokers, 20 smokers with normal lung function and 20 smokers with moderate COPD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
1
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 32 publications
2
42
1
6
Order By: Relevance
“…At the same time, these changes could be the first step towards tumour genesis, as it is now known that Treg cells decrease cellular immune anti-tumour defence [3]. Opposite changes in peripheral airways in COPD patients which we reported in our article, possibly enhance the autoimmune process [1]. Therefore, the events occurring in central and peripheral airways should be regarded as independent local reactions of the immune system.…”
mentioning
confidence: 51%
“…At the same time, these changes could be the first step towards tumour genesis, as it is now known that Treg cells decrease cellular immune anti-tumour defence [3]. Opposite changes in peripheral airways in COPD patients which we reported in our article, possibly enhance the autoimmune process [1]. Therefore, the events occurring in central and peripheral airways should be regarded as independent local reactions of the immune system.…”
mentioning
confidence: 51%
“…We also found an increased proportion of these cells in BALF from lung cancer patients: the mean proportion of CD4+/CD25+ in the CD4+ population was 47% in cancer patients and was higher than that in patients with interstitial lung disease (14%) [7]. Therefore, the results of ISAJEVIS et al [1] who found that FOX3 positive cells are upregulated in large airways and downregulated in the small airways could be affected by tumour stage and location.…”
Section: To the Editorsmentioning
confidence: 70%
“…We read with great interest the paper by ISAJEVS et al [1] published recently in the European Respiratory Journal. The role of regulatory cells in the pathomechanism of chronic obstructive pulmonary disease (COPD) is an interesting issue and has been the subject of our studies on the systemic effects in COPD.…”
Section: To the Editorsmentioning
confidence: 95%
“…In other studies, the lungs of smokers with COPD and emphysema have been found to have fewer Tregs and less FoxP3 mRNA than the lungs of healthy smokers, who had more Tregs than the nonsmokers [19,20]. Furthermore, smokers with COPD were found to have an upregulation of FoxP3+ T-cells in the large airways, but had a downregulation of FoxP3+ T-cells in the small airways, the main site of pathological involvement in COPD, which correlated with airflow limitation [21]. This suggests that in smokers with normal lung function or mild COPD, Tregs, by controlling the immune reaction, might prevent the development of severe disease.…”
Section: How Could the Inflammation Be Suppressed?mentioning
confidence: 99%